Kajian Literatur: Penerapan Good Corporate Governance Terhadap Integritas Laporan Keuangan - Maya Letisia; Yusnia Fauziah; Mohammad Djasuli (Jurnal Ekonomika Dan Bisnis, 2022)
This research is basically conducted to examine more deeply about the influence of good corporate governance on the integrity of financial statements. The research method used is a literature study by observing articles related to good corporate governance and the integrity of financial statements. In this study, the influence of good corporate governance is proxied by institutional ownership, managerial ownership, independent commissioners and audit committees. The results of the research show that previous studies that tested the effect of good corporate governance on the integrity of financial statements stated contradictory results, so that further research is needed in a broader and more in-depth manner to obtain appropriate results and can be applied by interested parties in the real world.